International Monetary Fund Annual Report 1962. (Annual Report of the Executive Board; Annual Report of the Executive Board, 1962)
This paper reviews key findings of the IMF's Annual Report for the fiscal year ended April 30, 1962. The report highlights that the year 1961 was one of general expansion in the industrial countries. In the United States and Canada, industrial production and real national product resumed their upward course during the spring of 1961, following the mild recession of 1960. Expansion continued in Europe and Japan, although at a slower rate than in the earlier year, as production approached the limits of the available supplies of labor.